2019
DOI: 10.1371/journal.pcbi.1006822
|View full text |Cite
|
Sign up to set email alerts
|

Efficient neural decoding of self-location with a deep recurrent network

Abstract: Place cells in the mammalian hippocampus signal self-location with sparse spatially stable firing fields. Based on observation of place cell activity it is possible to accurately decode an animal’s location. The precision of this decoding sets a lower bound for the amount of information that the hippocampal population conveys about the location of the animal. In this work we use a novel recurrent neural network (RNN) decoder to infer the location of freely moving rats from single unit hippocampal recordings. R… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 41 publications
0
38
1
Order By: Relevance
“…In particular, including pairwise (Pillow et al, 2008;Meshulam et al, 2017) or temporal (Naud and Gerstner, 2012) correlations of neuronal activity could reduce decoding error. Note that these temporal correlations would also be taken into account when using long shortterm memory (LSTM) artificial neural networks (Tampuu et al, 2019), thus increasing reconstruction accuracy at the expense of interpretability. Rather than proposing a sophisticated analysis pipeline, the methods presented here have the advantage of remaining simple, requiring only few data points, and are easily interpretable using metrics that can facilitate the communication of results along with significance and confidence intervals, making it an appropriate tool for exploration of calcium imaging data in conjunction with behavior.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, including pairwise (Pillow et al, 2008;Meshulam et al, 2017) or temporal (Naud and Gerstner, 2012) correlations of neuronal activity could reduce decoding error. Note that these temporal correlations would also be taken into account when using long shortterm memory (LSTM) artificial neural networks (Tampuu et al, 2019), thus increasing reconstruction accuracy at the expense of interpretability. Rather than proposing a sophisticated analysis pipeline, the methods presented here have the advantage of remaining simple, requiring only few data points, and are easily interpretable using metrics that can facilitate the communication of results along with significance and confidence intervals, making it an appropriate tool for exploration of calcium imaging data in conjunction with behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that increased neuronal firing rates correlate strongly with feature importance when using LSTM RNN models for neural decoding 35 . Therefore, to investigate the effect of channel count on decoding performance, we ordered neural channels according to the highest neural activity (i.e., highest counts of threshold crossings) over the training data set.…”
Section: Resultsmentioning
confidence: 99%
“…However, the required skills can be developed within labs in a short time frame. As an example, we took two recently published papers in PLOS Computational Biology [ 3 , 4 ] and customized the code provided by the authors to create NeuroLibre-style Jupyter Books with interactive figures using Plotly ( Example 1 and Example 2 ). As part of an experimental collaboration between NeuroLibre and PLOS Computational Biology , the journal team is seeking user feedback on these examples to further understand the value of these features to the journal’s community.…”
Section: Details Of Analysismentioning
confidence: 99%